The Management of Multinational R&D: A Neglected Topic in International Business Research - Cheng, Joseph L. C.; Bolon, Douglas S. (Journal of International Business Studies, 1993)
Despite the growing involvement of multinational firms in foreign-based R&D during the past fifteen years, little research has been done on why and how firms internationalize their R&D and what effects it might have on firm competitiveness. The present paper calls attention to this neglect and seeks to advance the management of multinational R&D as an area of study for international business scholars. To this end, the paper first examines the key contributing factors to increased foreign R&D investments among multinationals. It then reviews the research literature to find out what we presently know about the management of multinational R&D. Finally, a research agenda is proposed to provide a foundation and stimulus for future investigations. Seven research directions are recommended, with an emphasis on interdisciplinary inquiry and a focus on issues that have both theoretical and practical significance.